2023
DOI: 10.3389/fimmu.2023.1178462
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of bacteriocinogenic and non-bacteriocinogenic Lactococcus cremoris of aquatic origin on rainbow trout (Oncorhynchus mykiss, Walbaum)

Abstract: Lactic Acid Bacteria (LAB) are a group of bacteria frequently proposed as probiotics in aquaculture, as their administration has shown to confer positive effects on the growth, survival rate to pathogens and immunological status of the fish. In this respect, the production of antimicrobial peptides (referred to as bacteriocins) by LAB is a common trait thoroughly documented, being regarded as a key probiotic antimicrobial strategy. Although some studies have pointed to the direct immunomodulatory effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Overall, the results of the study provide further evidence that biomarkers can have a negative impact on the adaptive immunity of fish. However, the severity of the impact appears to vary depending on the fish’s individual immune [ 53 ] response. Further studies are needed to better understand the mechanisms by which IBR affects the adaptive immunity of fish, and to develop effective strategies for preventing and treating the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results of the study provide further evidence that biomarkers can have a negative impact on the adaptive immunity of fish. However, the severity of the impact appears to vary depending on the fish’s individual immune [ 53 ] response. Further studies are needed to better understand the mechanisms by which IBR affects the adaptive immunity of fish, and to develop effective strategies for preventing and treating the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Sadraei et al (2022) found that the cell proliferation and differentiation increased in bone marrow mesenchymal stem cells pretreated with nisin on a poly-L-lactic-acid scaffold. Moreover, a great number of studies have shown that nisin has immune regulation function (Contente et al, 2023;Jia et al, 2019;Malaczewska & Kaczorek-Lukowska, 2021;Malaczewska et al, 2019;Singh et al, 2014).…”
Section: Application In Medicine Fieldmentioning
confidence: 99%
“…This interest has been mostly directed towards vaccination and the use of probiotics. However, due to the immature state of the larvae immune system, which renders vaccination less effective and costlier, the interest for probiotic bacteria has been growing [2,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In aquaculture, probiotics can be defined as live micro-organisms, usually bacteria or yeasts, that, when administered through feed or the rearing environment, confer beneficial effects to the host such as protection against ichthyopathogens, the stimulation of the immune system, competition for adhesion sites in the mucosa, improved tolerance to stress, host nutrition enhancement, and water quality improvement [14][15][16][17][18]. Usually, both the host and the rearing environment have been regarded as the most suitable sources for the isolation of probiotic candidates for larviculture.…”
Section: Introductionmentioning
confidence: 99%